Analisis Integrasi Kearifan Lokal dalam Pembelajaran Sains dan Pengaruhnya terhadap Keterampilan Abad 21: Tinjauan Pustaka - Kamila Kamila; Insih Wilujeng; Jumadi Jumadi; Shanty Yustin Ungirwalu (Postgraduate, University of Mataram, 2024)
Integrating local potential in science learning is an effort to introduce culture to the younger generation by linking indigenous knowledge into scientific knowledge. This study focuses on examining research conducted in the past five years, specifically those published in SINTA 2 to 4, that delve into the integration of local potential in science learning. The research employs a qualitative approach, utilizing a literature review of 30 articles chosen based on their classification, which explores the fusion of local potential and the unique culinary traditions of a region in science education. The results of the papers are in the form of classification for educational research in the fields of science, physics, chemistry, and biology. The results of the analysis show that the integration of local potential in science learning is combined with learning models and methods such as STEAM, Inkuriri, Discovery Learning, using PBL and PJBL models. Integration of local potential in science learning can improve 21st century skills including learning outcomes, concept understanding, critical thinking skills, problem solving skills, environmental literacy and students' love for local culture and problem-solving skills. The most significant results are learning outcomes and understanding of student concepts.